Mice Cohabiting With Familiar Conspecific in Chronic Stress Condition Exhibit Methamphetamine-Induced Locomotor Sensitization and Augmented Consolation Behavior - Carneiro de Oliveira, Paulo Eduardo; Carmona, Isabela Miranda; Casarotto, Mariana; Silveira, Lara Maria; Oliveira, Anna Cecília Bezerra; Canto-de-Souza, Azair (Frontiers in Behavioral Neuroscience, 2022)
Recognize and share emotions are essential for species survival, but in some cases, living with a conspecific in distress condition may induce negative emotional states through empathy-like processes. Studies have reported that stressors promote psychiatric disorders in both, who suffers directly and who witness these aversive episodes, principally whether social proximity is involved. However, the mechanisms underlying the harmful outcomes of emotional contagion needs more studies, mainly in the drug addiction-related behaviors. Here, we investigated the relevance of familiarity and the effects of cohabitation with a partner submitted to chronic stress in the anxiety-like, locomotor sensitization and consolation behaviors. Male swiss mice were housed in pairs during different periods to test the establishment of familiarity and the stress-induced anxiety behavior in the elevated plus maze. Another cohort was housed with a conspecific subjected to repeated restraint stress (1h/day) for 14 days. During chronic restraint the allogrooming was measured and after the stress period mice were tested in the open field for evaluation of anxiety and locomotor cross-sensitization induced by methamphetamine. We found that familiarity was established after 14 days of cohabitation and the anxiogenic behavior appeared after 14 days of stress. Repeated restraint stress also increased anxiety in the open field test and induced locomotor cross-sensitization in the stressed mice and their cagemates. Cagemates also exhibited increase in consolation behavior after stress sessions when compared to control mice. These results indicate that changes in drug abuse-related, consolation and affective behaviors may be precipitate through emotional contagion in familiar conspecifics.